Pengaruh kompetensi aparatur pemerintah, partisipasi masyarakat, Sistem Pengendalian Intern Pemerintah (SPIP) dan gaya kepemimpinan terhadap good governance pada pengelolaan keuangan SKPD Kabupaten Balangan - Erliyanti, Erliyanti; Yuliani, Rahma; Hamdani, Hamdani (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
The implementation of good governance is very important that there are several variables that have a strong influence on good governance. This study examines the influence of (1) the relationship between government apparatus competence on good governance in financial management of the SKPD Kabupaten Balangan, (2) the relationship between public participation on good governance in financial management of the SKPD Kabupaten Balangan, (3) the relationship between Government Internal Control System (SPIP) on good governance in in financial management of the SKPD Kabupaten Balangan, and (4) the relationship between leadership style on good governance in financial management of the SKPD Kabupaten Balangan The population in this study were employees in the financial sectore at 41 SKPD in SKPD Kabupaten Balangan and auditor in Kabupaten Balangan, numbering 287 people. While the sample size were 138 persons, including 123 people from three respondents in each SKPD and 15 people from auditor. The sampling technique used was purposive sampling. The method of collection data is based on questionnaire (questionnaire). Data analysis technique used are multiple regression analysis and SPSS version 25.The analysis found that government apparatus competency, community participation, and the government's internal control system (SPIP) have positive effect on good governance in financial management of the SKPD Kabupaten Balangan. Meanwhile, the leadership style has no effect on good governance in in financial management of the SKPD Kabupaten Balangan.